THE DEVELOPMENT OF SCIENTIFIC-APPROACH-BASED LEARNING INSTRUMENTSINTEGRATED WITH RED ONION FARMING POTENCY IN BREBES INDONESIA (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2016)
This study aimed to describe the eligibility category of science learning instrument based on scientific approach integrated with onion farming potency. Also, this study aimed to analyze the effectiveness of the application of the science learning instrument in terms ofscience process skills development and the cognitive learning outcomes in the student of class VII SMPN 1 Bulakamba.This study used thedevelopment research methods by adapting the 4D model that includes define, design, develop, and disseminate. The learning instruments developed in this research were the learning implementation plan (RPP) and the student worksheet (LKS). The data collection was done by using non-test technique using interview guides, product validation sheet, students’ response sheet to the readability of LKS and the instructional observation sheets; as well as using theworksheet of process skills and cognitive learning outcomes. The results showed that the eligibility of the science learning instruments integrated with onion farming potency was categorized as excellent. The application of scientific-approach-based learning instruments was effective to improve the process skills and the students’ cognitive learning outcomes in class VII SMPN 1 Bulakamba.